Perancangan Sistem Informasi Anggaran Pendapatan Belanja Daerah Kecamatan Dengan Metode Line-Item Budgeting - Tafonao, Riama; Hondro, Rivalri K; Panjaitan, Melda (Bulletin of Data Science, 2023)
With current technological developments, each agency is expected to be able to create a regional revenue and expenduture budget information system. The budget information system and regional expenditure revenue can help government agencies, especially the sub-district office in Medan, in making budget financial reports and realization reports, so as to facilitate programming of VB Net and MySQL databases. The facilitation contained in this regional revenue and expenditure budget information sustem includes input of budget account data, budget transaction forms, realization forms, budget reports and budget realization reports. Main Key : information systems, vasual basic.net 2010, mysql, regional APBD, Regional Revenue and Expenditure Budget.